Challenges and Opportunities for Learning Arabic: Insights from Non-native Students in Indonesian Higher Education - Muassomah, Muassomah; Hakim, Arief Rahman; bin Yahaya, Mohd Firdaus (LISANIA: Journal of Arabic Education and Literature, 2025)
This study investigates the challenges and opportunities faced by non-native students in Indonesia in learning Arabic. With a focus on the context of higher education, this study uses a qualitative approach to analyze students' experiences in facing obstacles that may arise during the Arabic learning process. Data were collected through in-depth interviews and observations, enabling a deep understanding of the dynamics of Arabic language learning among non-native students. The results of this study provide an overview of challenges such as vocabulary acquisition, speech, and language environment, as well as differences in language structure. Meanwhile, it also identifies opportunities such as the development of cross-cultural communication skills and the strengthening of academic skills. The implications of these findings could provide a foundation for the development of more effective curriculum and learning strategies to support non-native students in overcoming challenges and taking advantage of opportunities in Arabic language learning.